Cloning, Expression and Purification of Putative Isovaleryl-CoA Dehydrogenase from Paracoccus denitrificans Pd1222 - Karim, Rafid M.; Hashim, Abdulkareem Jasim (Iraqi Journal of Science, 2022)
In Paracoccus denitrificans Pd1222 bacterium, Pden_3633 encoding gene has been nominated to encode for Isovaleryl CoA dehydrogenase (IVDH) [1], the enzyme which involve in leucine catabolism pathway. In this study, this putative IVDH was investigated. IVDH encoding gene from P. denitrificans Pd1222 in addition to desired features for cloning, expression and purification have been designed and synthesized. The synthetic coding sequence was expressed in Escherichia coli. The enzyme was purified as a Strep-Tagged protein with a total protein 220.5 mg. An apparent molecular weight of 42.9 kDa was determined on SDS gel. Amino acid alignment showed a very high similarity (91-96%) with corresponding IVDH from several other Paracoccus species. As for genera other than Paracoccus; Roseovarius mucosus, Catellibacterium nectariphilum and Oceanicola nanhaiensis recorded the highest similarity (85-86%), Suggesting that these mentioned species all have similar IVDH.